Development of a Short Form of the Five-Factor Narcissism Inventory: the FFNI-SF - Sherman, Emily D; Miller, Joshua D; Few, Lauren R; Campbell, W Keith; Widiger, Thomas A; Crego, Cristina; Lynam, Donald R (Psychological assessment, 2015)
The Five-Factor Narcissism Inventory (FFNI; Glover, Miller, Lynam, Crego, & Widiger, 2012) is a 148-item self-report inventory of 15 traits designed to assess the basic elements of narcissism from the perspective of a 5-factor model. The FFNI assesses both vulnerable (i.e., cynicism/distrust, need for admiration, reactive anger, and shame) and grandiose (i.e., acclaim seeking, arrogance, authoritativeness, entitlement, exhibitionism, exploitativeness, grandiose fantasies, indifference, lack of empathy, manipulativeness, and thrill seeking) variants of narcissism. The present study reports the development of a short-form version of the FFNI in 4 diverse samples (i.e., 2 undergraduate samples, a sample recruited from MTurk, and a clinical community sample) using item response theory. The validity of the resultant 60-item short form was compared against the validity of the full scale in the 4 samples at both the subscale level and the level of the grandiose and vulnerable composites. Results indicated that the 15 subscales remain relatively reliable, possess a factor structure identical to the structure of the long-form scales, and manifest correlational profiles highly similar to those of the long-form scales in relation to a variety of criterion measures, including basic personality dimensions, other measures of grandiose and vulnerable narcissism, and indicators of externalizing and internalizing psychopathology. Grandiose and vulnerable composites also behave almost identically across the short- and long-form versions. It is concluded that the FFNI-Short Form (FFNI-SF) offers a well-articulated assessment of the basic traits comprising grandiose and vulnerable narcissism, particularly when assessment time is limited.